Hormonal Male Contraception: Getting to Market - Page, Stephanie T.; Blithe, Diana; Wang, Christina (Frontiers in Endocrinology, 2022)
Rates of unplanned pregnancies are high and stagnant globally, burdening women, families and the environment. Local limitations placed upon contraceptive access and abortion services exacerbate global disparities for women. Despite survey data suggesting men and their partners are eager for expanded male contraceptive options, efforts to develop such agents have been stymied by a paucity of monetary investment. Modern male hormonal contraception, like female hormonal methods, relies upon exogenous progestins to suppress the hypothalamic-pituitary-gonadal axis, in turn suppressing testicular testosterone production and sperm maturation. Addition of an androgen augments gonadotropin suppression, more effectively suppressing spermatogenesis in men, and provides androgenic support for male physiology. Previous contraceptive efficacy studies in couples have shown that hormonal male methods are effective and reversible. Recent efforts have been directed at addressing potential user and regulatory concerns by utilizing novel steroids and varied routes of hormone delivery. Provision of effective contraceptive options for men and women is an urgent public health need. Recognizing and addressing the gaps in our contraceptive options and engaging men in family planning will help reduce rates of unplanned pregnancies in the coming decades.